Implementation science frameworks used to implement evidence-based practice in nursing: An integrative review. - Ferreira, Stephani Amanda Lukasewicz; Alves, Náthalli Cristina Paim; da Rosa, Ninon Girardon; Primo, Cândida Caniçali; de Fátima Lucena, Amália (Applied Nursing Research, 2026)
Nurses' understanding of real-world challenges is crucial for bridging the gap between research and practice. Implementation science (IS) is one of the methods to reduce this gap; questions remain about how nursing has used IS and what frameworks have been proposed for implementing evidence-based practices (EBP). This integrative review aimed to identify frameworks used to implement EBP in the nursing field. This integrative review aimed to identify the frameworks of IS used by the nursing team to implement EBP. Authors searched six databases for studies published between 2006 and 2024, that focused on what frameworks nurses use to implement EBP. Two reviewers screened and selected studies, with a third resolving disagreements. Data on frameworks, area of intervention, patients under intervention, and EBP of the study were extracted and analyzed. The search identified 109 studies for analysis. The majority of these was published after 2020 and was performed in a hospital setting. The review found 14 distinct frameworks, with the most frequent being the Consolidated Framework for Implementation Research (CFIR), Theoretical Domains Framework (TDF), i-PARIHS/PARIHS, Knowledge to Action (KTA), and Reach, Effectiveness, Adoption, Implementation, Maintenance (RE-AIM) model. This review identified the implementation science frameworks used by nurses to bridge the research-practice gap and improve patient care, highlighting a need for further exploration and broader adoption within nursing. Not registered. What is already known • Implementation science is essential in bridging the gap between scientific knowledge and everyday practice in healthcare services. • Nurses play a central role in implementation science. Knowledge of implementation science frameworks remains limited within the profession, creating a gap between clinical intention and sustainable outcomes. What this paper adds • The high usage of determinant frameworks by nurses underscores the profession's strategic role in diagnosing contextual and organizational barriers before implementation. • The geographic and setting concentration (Americas and hospitals) reveals the demand of resource allocation and policy focus to expand implementation science within primary and community care settings. • Policy should recommend the application of evaluation frameworks to systematically assess real-world impact and support the long-term sustainability of EBP in health systems. • This review suggests using determinant frameworks to diagnose unit culture, process models to provide a roadmap for bedside adaptation, and evaluation frameworks to measure long-term sustainability.